USAID Feed the Future Kenya Accelerated Value Chain Development (AVCD) – Potato Value Chain. Endline Survey Report - International Potato Center (International Potato Center, 2020)
Potato farmers increased yields by 49% from 7.7 to 11.5 t/ha as a result of applying CIP-CG productivity-enhancing technologies and farmer training on learning farms. The results revealed that women are at equal with their male counterparts in terms of the area under improved technologies unlike baseline where there was great disparity in terms technologies applied by different gender categories. Value of sales from potato contributed 4.9 million USD to economies of the two intervention counties.